The Dilemma of Fresh Flower Farmers in Responding to the COVID-19 Pandemic (Case Study in Gunungsari Village, Batu) - Wahyudi, Fidela Dzatadini; Wisadirana, Darsono; Chawa, Anif Fatma (Sekolah Pascasarjana Universitas Brawijaya, 2024)
This study aimed to determine the form or type of dilemma experienced by fresh rose farmers in responding to the COVID-19 pandemic. This study was conducted in Gunungsari Village, Bumiaji Sub-District, Batu, the largest fresh flower cultivation center in East Java. This study used a qualitative research approach with a case study design to utilize James C. Scott’s theory of survival mechanisms in its analysis. The results showed that there were three types of dilemmas experienced by fresh flower farmers, namely (1) the dilemma of converting the type of work, (2) the dilemma of conversion of plant commodity types, and (3) the dilemma of the continuity of fresh flower farming. Although farmers essentially take action to minimize risk, as stated by Scott, there are differences in the causative factors because this study was conducted when a non-natural disaster of the COVID-19 pandemic occurred, which no one could predict when it would end. Keywords: dilemma, farmers, fresh flower farmers, survival mechanism, COVID-19 pandemic